2018
DOI: 10.1016/j.ophtha.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on Diabetic Eye Care

Abstract: Diabetes mellitus (DM) is a global epidemic and affects populations in both developing and developed countries, with differing health care and resource levels. Diabetic retinopathy (DR) is a major complication of DM and a leading cause of vision loss in working middle-aged adults. Vision loss from DR can be prevented with broad-level public health strategies, but these need to be tailored to a country's and population's resource setting. Designing DR screening programs, with appropriate and timely referral to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
308
1
19

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 567 publications
(331 citation statements)
references
References 78 publications
3
308
1
19
Order By: Relevance
“…The ICO currently also supports repeating screening up to 2 years. Along with the lead of key international guidelines,22 70 it is likely that more countries will start adopting a biennial screening approach for patients with no DR in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ICO currently also supports repeating screening up to 2 years. Along with the lead of key international guidelines,22 70 it is likely that more countries will start adopting a biennial screening approach for patients with no DR in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we determined the availability and variability of national DR screening guidelines in Asian countries, summarised their recommendations and compared them with the gold standard, Guidelines For Diabetic Eye Care by the International Council of Ophthalmology (ICO), which is an authoritative international organisation consisting of 120 national and subspecialty member societies from around the globe 22. Areas for improvement have been identified and may serve as a feedback for future versions of guidelines, in an effort to effectively combat DR-related vision loss in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Tight glycemic control decreases the onset of DR by 76% and delays the progression of DR by 54% [10]. Frequent screening for the early detection of DR along with appropriate, timely, effective treatment reduces blindness by as much as 98% [11]. In addition, several studies have reported that the control of hypertension and dyslipidemia improved patient outcomes and reduced the risk of blindness by 24% [12].…”
Section: Introductionmentioning
confidence: 99%
“…This goal can be achieved by multi-level public health strategies, starting with increasing public awareness and implementing evidence-based national screening programs for all patients with diabetes that ensure timely referral and timely, appropriate treatment. However, these need to be adjusted according to each country's resource settings and population characteristics [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although accumulating evidence suggest that the eyes of patients with DM can have histological and/or functional retinal changes even before the onset of clinically detectable microvascular damage, 2-4 the gold standard classification of DR is based on funduscopically apparent clinical signs secondary to severely impaired retinal vasculature. 5 The Early Treatment Diabetic Retinopathy Study classification according to vascular abnormality has been used in many randomized controlled trials (RCTs). However, although one intervention (intensive blood sugar control) decreased the risk of DR development and/or progression, there remains a large number of patients with vision loss in almost all RCTs, suggesting that funduscopy-based DR classification is not sufficient to maintain long-term good vision in diabetic eyes.…”
Section: Introductionmentioning
confidence: 99%